THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE OF PT RAMAYANA LESTARI SENTOSA TBK (CIPLAZ) MARGONDA DEPOK - Bunga Astra Gracia; Indri Rahayu (PT. Intelek Cendikiawan Nusantara, 2025)
This research aims to analyze the influence of organizational culture and work discipline on employee performance at PT. Ramayana Lestari Sentosa Tbk. This research used a quantitative method and to determine the sampling using the Slovin formula. The population is 181 so there are 82 respondents among PT employees. Ramayana Lestari Sentosa Tbk. Then it was analyzed using multiple linear regression analysis with the help of SPSS version 25 software. The research results showed that organizational culture and work discipline had a significant influence, both partially and simultaneously, on employee performance. The t- test shows that organizational culture has a significant influence with a t- value of 9.307 > t-table 1.664 and a significance value of 0.000 < 0.05. Work discipline also has a significant influence with a t-value of 12.547 > t-table 1.664 and a significance value of 0.000 < 0.05. Simultaneously, organizational culture and work discipline influence employee performance with a F-count of 96.962 and a significance of 0.000, which is smaller than 0.05. The coefficient of determination (R2) of 0.711 indicates that 71.1% of the variation in employee performance can be explained by organizational culture and work discipline.